2009
DOI: 10.1103/physrevlett.102.147201
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric Memory Effect of the Nonpolar Phase with Collinear Spin Structure in MultiferroicMnWO4

Abstract: The novel memory effect of a nonpolar paraelectric phase with a collinear spin structure has been observed in a magnetoelectric multiferroic material MnWO4. Since the ferroelectric polarization arises from a noncollinear spin structure, in a new class of magnetoelectric multiferroic materials with a spiral-spin structure, the information of ferroelectric domains should be lost in the collinear spin phase. However, in MnWO4, it has been found that the domain states in the ferroelectric phase are memorized even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 27 publications
9
41
0
Order By: Relevance
“…This is an essential difference to MnWO 4 where the incommensurate magnetic modulation is much further away from the commensurate value. Anharmonic components were also observed in the AF2 phase of MnWO 4 22 and there they are related with magnetoelectric memory effects observed for the electric-field control of multiferroic domains 23,24 .…”
Section: Microscopic Measurementsmentioning
confidence: 91%
“…This is an essential difference to MnWO 4 where the incommensurate magnetic modulation is much further away from the commensurate value. Anharmonic components were also observed in the AF2 phase of MnWO 4 22 and there they are related with magnetoelectric memory effects observed for the electric-field control of multiferroic domains 23,24 .…”
Section: Microscopic Measurementsmentioning
confidence: 91%
“…19,20 More recently, the magnetoelectric memory effect was identified in MnWO 4 by applying a magnetic field. 21 In this series of works, much attention was paid to the direct observation of the ferroelectric polarization and its behavior under a magnetic field.…”
Section: 10mentioning
confidence: 99%
“…[4][5][6] Recent work has demonstrated that the ferroelectric and spin-spiral orders coexist and are intimately coupled in this material. [4][5][6][7][8][9][10][11] MnWO 4 undergoes three magnetic phase transitions in zero magnetic field below 14 K (Figure 1). 12 With decreasing temperature, MnWO 4 first transforms from a paramagnetic (PM) state to a collinear spin sinusoidal state (AF3) at T N ≈ 13.5 K, then to a tilted elliptical spiral spin state (AF2) at T 2 ≈ 12.3 K, and eventually to a up-up-down-down collinear spin structure (AF1) at T 1 ≈ 8.0 K. The magnetic structures of the AF3 and AF2 states are ICM to the lattice spacing with propagation vector k = (-0.214, 0.5, 0.457), while that of the AF1 state is commensurate (CM) with propagation vector k = (-0.25, 0.5, 0.5).…”
Section: Introductionmentioning
confidence: 99%